Pengembangan Media Pembelajaran Video Animasi Berbasis Canva pada Mata Pelajaran Informatika Kelas VII SMPI Al Fattahiyyah - Maskurun, Masfufah Aris; Pamungkas, Bian Dwi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to develop animated video learning media using Canva for the Grade VII Informatics subject at SMPI Al Fattahiyyah. The research employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate). The developed media was validated by subject matter experts and media experts, and tested on both small and large groups of students. Validation results from the media expert indicated a feasibility score of 91.53% (categorized as very feasible), while the subject matter expert scored it at 71.66% (categorized as feasible). The practicality test results from small and large student groups showed percentages of 88.5% and 89.25%, respectively, categorized as very practical. The media was considered engaging, easy to use, and relevant to the Informatics subject matter, particularly in the topic of data analysis using Excel. However, some limitations were noted, such as the lack of interactive features and dependency on internet connectivity. Overall, the Canva-based animated video learning media is considered suitable as an alternative teaching tool that can enhance students’ learning interest and support digital-based learning environments.